2008
DOI: 10.1002/hep.22395
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of T cell tolerance induction by murine hepatic Kupffer cells

Abstract: The liver is known to favor the induction of immunological tolerance rather than immunity. Although Kupffer cells (KC) have been indicated to play a role in liver tolerance to allografts and soluble antigens, the mechanisms involved remain unclear. We hypothesized that KCs could promote immune tolerance by acting as incompetent antigen-presenting cells (APC), as well as actively suppressing T cell activation induced by other potent APCs. The expression of antigen presentation-related molecules by KCs was pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
209
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(221 citation statements)
references
References 74 publications
2
209
0
6
Order By: Relevance
“…Antigenspecific regulatory CD4 + T-cell generation requires antigenpresenting cells help. Previous studies showed that liver resident Kupffer cells (KCs) have the potential to induce T-cell tolerance in liver (25,26). In our model, we found IL-10 and IFN-γ production significantly decreased in hepatic MNCs from KCdepleted HBV-injected mice (Fig.…”
Section: Resultssupporting
confidence: 52%
“…Antigenspecific regulatory CD4 + T-cell generation requires antigenpresenting cells help. Previous studies showed that liver resident Kupffer cells (KCs) have the potential to induce T-cell tolerance in liver (25,26). In our model, we found IL-10 and IFN-γ production significantly decreased in hepatic MNCs from KCdepleted HBV-injected mice (Fig.…”
Section: Resultssupporting
confidence: 52%
“…KCs are important in chronic inflammatory liver injury because they influence the functions of liver, hepatic stellate, and endothelia cells (Kolios et al, 2006;Tavares et al, 2013;You et al, 2008). Nuclear factor kB (NFkB) and p38 are involved in several inflammatory cytokine responses such as the pathways that mediate endotoxins that cause liver damage (Kolios et al, 2006;Luckey & Petersen, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…2 Nonparenchymal liver cells, including liver sinusoidal endothelial cells, dendritic cells (DCs) and Kupffer cells (KCs), have been shown to be responsible for the creation of a local immunosuppressive microenvironment, permitting immune effector cells, such as T cells, to deliver tolerogenic signals, which contributes to the tolerogenic properties of the liver. [3][4][5][6] However, the exact mechanisms for the hepatic immunosuppressive microenvironment remain to be fully understood.…”
mentioning
confidence: 99%